Hilangnya karakter pedestrian shopping street Jalan Tunjungan akibat transformasi Surabaya sebagai Kota Metropolitan (ARTEKS : Jurnal Teknik Arsitektur, 2019)
The loss of pedestrian shopping street characters in Jalan Tunjungan due to the transformation of Surabaya as a Metropolitan City In general, there are centers of commercial activity in a city. Through the patterns of development of commercial activities, a pedestrian shopping street typology which prioritizes pedestrians in its pattern and activity system was born. Jalan Tunjungan Surabaya represents this typology well because it was developed to be a pedestrian-based shopping area in Gemeente government era. Along with the development of Surabaya, the uniqueness of the urban artefact of Tunjungan area is transformed and being dominated by multi-storey buildings and Jalan Tunjungan became a city axis. The uniqueness of Jalan Tunjungan which was able to attract tourists is endangered due to the demands of Surabaya's economic development. Through a synchronic-diachronic approach with qualitative-descriptive methods, this study aims to identify patterns, types, and systems that create the physical-spatial characteristics of pedestrian shopping street in Jalan Tunjungan that has remained adapted and lost due to the transformation of Surabaya as a metropolitan city. Through comparative analysis, the findings conclude that the only thing remains is the linearity pattern of the building structure, while the type of road is adapted into one-way avenue with planned lane division and the addition of on-site parking system. Building types is adapted into commercial buildings. The characteristics of the arcades in some buildings are lost, the transportation system removes the passenger stop, the bridge is no longer being used, and the pedestrian pattern is disrupted due to the pattern of traffic. Jalan Tunjungan, which used to prioritize the experience of shopping by walking, has been degraded to a shopping street area.© 2019 Anneke Clauvinia Patriajaya, Yohanes Karyadi Kusliansjah
Keywords: Jalan Tunjungan; Loss of character; Pedestrian shopping street; Surabaya Metropolitan City; Transformation